1991
DOI: 10.1182/blood.v77.3.637.bloodjournal773637
|View full text |Cite
|
Sign up to set email alerts
|

The effect of N-alkyl modification on the antimalarial activity of 3- hydroxypyridin-4-one oral iron chelators

Abstract: The antimalaria effect of iron chelators is attributed to their interaction with a labile iron pool within parasitised erythrocytes, and it was postulated that increased affinity to iron as well as increased lipophilicity may improve antimalarial activity. In the present study we have examined the antimalarial effect of 3- hydroxypyridin-4-ones, a family of bidentate orally effective iron chelators whose lipophilicity may be modified by altering the length of the R2 substituent on the ring nitrogen. A signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 0 publications
2
22
0
Order By: Relevance
“…For example, deferiprone levels of 5-15 mol/L produced only 38-52% inhibition of parasite growth in vitro. 11,12 Thus, the findings serve to emphasize that sustained exposure to effective concentrations of an iron-chelating agent is required for an anti-plasmodial effect.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…For example, deferiprone levels of 5-15 mol/L produced only 38-52% inhibition of parasite growth in vitro. 11,12 Thus, the findings serve to emphasize that sustained exposure to effective concentrations of an iron-chelating agent is required for an anti-plasmodial effect.…”
Section: Discussionmentioning
confidence: 91%
“…Our pharmacokinetic study indicated that the subjects achieved a mean peak plasma deferiprone level of 108.9 mol/L after a dose of 25 mg/kg, which is within the range of concentrations that result in 85-100% inhibition of parasite growth in vitro. [11][12][13] While the peak deferiprone levels were in the range expected for effective anti-plasmodial activity, the drug was administered every 6-8 hr during the study and the t 1/2 was only 92 min. Considering the findings of other investigators, 11,12 these pharmacokinetic results suggest that plasma concentrations of deferiprone with effective anti-malarial activity were maintained only for intermittent brief periods during the therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The narcotic analgesics are potent but have several undesirable actions and their use leads to dependence. It is well known that 4(1H)-pyridinone derivatives have shown various pharmacological effects such as antibacterial [1,2], antifungal [3], antimalarial [4,5], cardiotonic agents [6], antihypertensive [7], antineoplastic [8][9][10][11], anti-inflammatory [12], analgesic effects [13][14][15][16], and favourable effect in Parkinson's disease [17,18]. Especially 1,2-dimethyl and 1,2-diethyl-3hydroxy-4(1H)-pyridinone derivatives have shown chelating effect [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28][29] Importantly, the antimalarial activity of iron chelating agents has been established both in vitro and in vivo. [28][29][30][31] In addition, compound 1 has been shown to exhibit significant protective effects against DNA damage by hydroxyl radicals generated from the Fenton reaction via iron chelation, as well as free radical-scavenging activity. 23 Encouraged by the antimalarial data of 1, we subsequently performed substructure searching on an in-house natural product library using the spermidine fragment in an attempt to identify additional polyamine alkaloids for antiplasmodial evaluation.…”
mentioning
confidence: 99%